Evaluation of Prebiotic Effects of High-Purity Galactooligosaccharides in vitro and in vivo - Hong, Ki Bae; Kim, Jae Hwan; Kwon, Hyuk Kon; Han, Sung Hee; Park, Yooheon; Suh, Hyung Joo (Food Technology and Biotechnology, 2016)
Galactooligosaccharides (GOS) are an important class of dietary prebiotics that exert beneficial effects on intestinal microbiota and gut barrier function. In this study, high-purity GOS (HP-GOS) were investigated and and confirmed as prebiotic ingredients in rat diet. HP-GOS were successfully produced using a two-step process, enzymatic hydrolysis and fermentation by yeast. They were found to serve as a good substrate and carbon source for supporting the growth of probiotic bacteria more effectively than other commercial GOS. Following administration of 1% (by mass) of HP-GOS to rats, the growth of and in the gut increased most rapidly up to 12 h, and thereafter the increase was slow. Therefore, 1% HP-GOS was found to be acceptable for the growth of probiotic bacteria. Groups of animals that were orally administered HP-GOS and bifidobacteria during the study, and the group administered HP-GOS during the 2nd (days 13-15) and 4th (days 28-30) period of the study had significantly (p<0.05) higher numbers of bifidobacteria in faeces than groups receiving a single dose of bifidobacteria. HP-GOS affected the expression of genes encoding glucagon-like peptide-1 (GLP-1) and peptide YY (PYY). There was a significant upregulation of GLP-1 and PYY mRNA with HP-GOS and bifidobacteria intake. We propose that the prebiotic properties of HP-GOS are potentially valuable for the production of functional foods for human consumption.